A review on the state of cost data inputs of Life Cycle Cost (LCC) for rigid pavement maintenance and rehabilitation in Malaysia - Ahmad Jasmi, Siti Zulaiha; Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin; Mohd Rahim, Faizul Azli (Faculty of Built Environment, University Malaya, 2018)
Many scholars asserted that LCC plays an important role in the cost estimation of rigid pavement due to high construction, maintenance and reconstruction costs in Malaysia. Due to high budget allocation and expenditure on the maintenance and rehabilitation works of pavements in Malaysia by the government, it is crucial for the transportation agencies to optimize the budget allocation and select the most cost-effective pavement maintenance and rehabilitation alternatives. LCC is a useful economic assessment technique that compares the cost-effectiveness of different maintenance and rehabilitation approaches within the same road pavement type. However, in order to produce a comprehensive and reliable LCC output, there is need to ensure the cost data inputs is ready and quality enough to be used in the LCC estimation. This paper presents the outcomes of the comprehensive literature review on the state of cost data inputs for LCC analysis of rigid pavement maintenance and rehabilitation in Malaysia. The outcomes of the literature study have established that the majority of the construction industry key players are aware LCC analysis should be practiced in the rigid pavement maintenance and rehabilitation. However, the current state of LCC practice of rigid pavement maintenance and rehabilitation in Malaysia is still at the infancy stage and unready to be implemented due to the difficulties in attaining quality cost data for generating a comprehensive and reliable LCC analysis. The findings provide information on the current state of cost data inputs of LCC analysis of rigid pavement maintenance and rehabilitation in the Malaysian construction industry.